DAMPAK TINDAK PIDANA PENCUCIAN UANG TERHADAP STABILITAS EKONOMI DAN KEPERCAYAAN PUBLIK - Ibnurozi Khalid Darmawan; Saiful Bahri; Saddam Hosen (PT. Hasba Edukasi Mandiri, 2025)
Money laundering (ML) has become a critical issue in the global economy, including in Indonesia, as it can undermine economic stability and public trust in the financial system. In Indonesia, Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering is the primary legal framework to address this issue. However, despite clear regulations, the implementation and enforcement of laws related to ML face various challenges, such as the lack of coordination among supervisory agencies and imperfections in the suspicious transaction reporting system. This article evaluates the effectiveness of the law, compares it with international policies, and provides recommendations for strengthening Indonesia's legal and policy framework. The use of advanced technology, capacity building for supervisory agencies, and better coordination among relevant agencies are key to effectively combating ML.